Portraits of Puppet Art Thimplong at District Nganjuk: Reduction of Local Culture in the Acceleration of Nowadays Era - Latif Kusairi; Depy Tri Budi Siswanto (Institut Agama Islam Negeri Salatiga, 2020)
This paper studies on how puppets as a media for preaching. One of them is puppet Thimplong brought by Eyang Sariguna. This puppet settings come from the Kingdoms of Kediri, Jenggala, Majapahit, Babad Tanah Jawi, and legends around Nganjuk. Currently, this puppet is rarely used and almost extinct. Therefore, the acceleration between this puppet and modern culture is needed for gaining acceptance among societies.